Perencanaan Program Pelatihan Masyarakat dalam Mendukung Agenda Prioritas Pembangunan Desa (Studi pada Kementerian Desa, Pembangunan Daerah Tertinggal, dan Transmigrasi) - Nirmaya, Gilar Cahya (Jurnal Ilmiah Administrasi Publik, 2019)
The Ministry of Village released a training program aimed at increasing the capacity villagers as the subject of development. This study attempts to describe the planning of the training through critical events model, the challenges, and the strategy to overcome challenges. The method of this research using qualitative approach. Hence, the research indicated that the planning majorly equipped critical events model. The challenge is in the role of politicians in determining training policy; causing the use of top down approach. The alternative strategy consists of: identifying the basic necessities of villagers in relation to skills needed, leveling each identified training, and identifying learners-need to determine the level of training.